Studi Penggunaan Aspal Buton Pada Lapisan Permukaan Jalan Raya - Aminsyah, Muhammad (Universitas Andalas, 2024)
Buton Asphalt (Asbuton) is a natural asphalt found on Buton Island, Southeast Sulawesi Province, located 1.5 meters above the ground and has been utilized. This asphalt was first discovered in 1926 by Hetzel, a Dutch geologist, which was then processed by PT Perusahaan Aspal Negara until finally implemented (one of them) by PT Sarana Karya (BUMN). This asphalt is a mixture of bitumen with other mineral materials in the form of rocks. This study aims to determine the performance characteristics of the surface layer mixture using Buton Asphalt on flexible road pavements. There are four variations of aggregate mixtures in this study, namely a mixture with the use of oil asphalt as a comparison and 3 Buton asphalt mixtures with variations in aggregate gradation. The type of mixture used is AC-BC. The use of Buton Asphalt with aggregate gradation based on the middle limit of the specification produces the best Marshall performance with an increase in stability value of 23.92%.